TECHNOLOGY FOR DEVELOPING INTELLECTUAL AUTONOMY AND PEDAGOGICAL ERUDITION BASED ON CREATIVE TASKS (Universal International Scientific Journal, 2026)
This thesis analyzes the theoretical and practical aspects of technologies for developing intellectual autonomy and pedagogical erudition based on creative tasks. It also examines the role of creative tasks in activating the educational process, enriching their pedagogical erudition, and forming independent thinking skills in students.
Keywords: : creative tasks, intellectual autonomy, pedagogical erudition, development of creative and critical thinking